Erratum to: Search for new phenomena in final states with an energetic jet and large missing transverse momentum in pp collisions at √s=8 TeV with the ATLAS detector (Eur. Phys. J. C (2015) 75:299, 10.1140/epjc/s10052-015-3517-3) - Onofre, A. (2015)
info:eu-repo/semantics/publishedVersion